Structural brain lesions and restless legs syndrome: a cross-sectional population-based study. Issue 11 (24th November 2014) - Rist, Pamela M; Tzourio, Christophe; Elbaz, Alexis; Soumaré, Aïcha; Dufouil, Carole; Mazoyer, Bernard; Kurth, Tobias
Abstract : Objective: To evaluate the association between white matter lesion (WML) volume, silent infarcts and restless legs syndrome (RLS) in a population-based study of elderly individuals. Design: Cross-sectional study. Setting: Population-based Three-City study. Participants: 1035 individuals from the Dijon, France, centre of the Three-City study who had available information on volume of WMLs from MRIs and who answered questions about the prevalence of RLS. Primary outcome measure: Prevalence of RLS. Results: WML volume was measured using an automated tissue segmentation method. Logistic regression was used to evaluate adjusted associations between tertiles of WML volume and RLS and between silent infarcts and RLS. 218 individuals (21.1%) were determined to have RLS. Compared with those in the first tertile of WML volume, individuals in the second tertile (OR=1.09; 95% CI 0.75 to 1.60) or third tertile (OR=1.17; 95% CI 0.79 to 1.74) did not have an increased prevalence of RLS. We also did not observe associations between the volume of deep or periventricular WML and RLS; nor did we observe an association between silent brain infarcts and RLS (OR=0.74; 95% CI 0.40 to 1.39). These findings were not modified by age or gender. Conclusions: Higher volume of WML and the presence of silent infarcts were not associated with an increased prevalence of RLS in this population-based cohort of elderly individuals.